The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/ncomms13353
|View full text |Cite
|
Sign up to set email alerts
|

Linear ubiquitin chain assembly complex coordinates late thymic T-cell differentiation and regulatory T-cell homeostasis

Abstract: The linear ubiquitin chain assembly complex (LUBAC) is essential for innate immunity in mice and humans, yet its role in adaptive immunity is unclear. Here we show that the LUBAC components HOIP, HOIL-1 and SHARPIN have essential roles in late thymocyte differentiation, FOXP3+ regulatory T (Treg)-cell development and Treg cell homeostasis. LUBAC activity is not required to prevent TNF-induced apoptosis or necroptosis but is necessary for the transcriptional programme of the penultimate stage of thymocyte diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 67 publications
3
56
1
Order By: Relevance
“…Hence, factors that affect thymocyte survival may impact on the development of MAIT cells as the gene encoding the MAIT TCR Vα‐chain (Vα19) is located at the extreme end of the 5′ end of the TCRα locus . Inhibitors of DNA transcription factors (Id2 and Id3), which interact with E proteins, have also been implicated in the development and differentiation of NKT cells, and more recently, we showed that members of the linear ubiquitin chain assembly complex, Hoil and Hoip, were required for normal NKT cell development in the thymus . Interestingly, the SLAM/SAP/Fyn pathway does not appear to be necessary for the development of MAIT cells, whereas it is important for the development of NKT cells .…”
Section: Factors That Regulate Mait Cell Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, factors that affect thymocyte survival may impact on the development of MAIT cells as the gene encoding the MAIT TCR Vα‐chain (Vα19) is located at the extreme end of the 5′ end of the TCRα locus . Inhibitors of DNA transcription factors (Id2 and Id3), which interact with E proteins, have also been implicated in the development and differentiation of NKT cells, and more recently, we showed that members of the linear ubiquitin chain assembly complex, Hoil and Hoip, were required for normal NKT cell development in the thymus . Interestingly, the SLAM/SAP/Fyn pathway does not appear to be necessary for the development of MAIT cells, whereas it is important for the development of NKT cells .…”
Section: Factors That Regulate Mait Cell Developmentmentioning
confidence: 99%
“…60 Inhibitors of DNA transcription factors (Id2 and Id3), which interact with E proteins, have also been implicated in the development and differentiation of NKT cells, [61][62][63][64] and more recently, we showed that members of the linear ubiquitin chain assembly complex, Hoil and Hoip, were required for normal NKT cell development in the thymus. 65 Interestingly, the SLAM/ SAP/Fyn pathway does not appear to be necessary for the development of MAIT cells, whereas it is important for the development of NKT cells. 16,[66][67][68][69] The use of MR1 tetramers in candidate gene knockout mice should lead to the discovery of key molecules that are important for the development of MAIT cells and these can be compared with those that regulate the development of NKT cells.…”
Section: Factors That Regulate Mait Cell Developmentmentioning
confidence: 99%
“…193,194 Recently, LUBAC activity has been reported to be required for late thymocyte differentiation, Treg development, and homeostasis, but was dispensable for the protection of Tregs against TNF-induced cell death. 195 On the other hand, deficiency for M1-deubiquitinase OTULIN leads to a severe spontaneous autoinflammation by T cell-specific NF-κB induction, as regulated cell death may not be activated properly. 196 It was thought that apoptosis might trigger the lethal phenotype of the TNFα-mediated shock and a study found the pan-caspase inhibitor zVAD-fmk to be protective in TNF-shock by inhibiting leukocyte apoptosis 199 ; however, later reports more reliably found that caspase inhibition by zVAD-fmk exacerbated the shock, resulting in TNF/ zVAD-mediated hyperacute shock.…”
Section: T-cell Function and Necroptosismentioning
confidence: 99%
“…Treg-specific HOIP ablation leads to lethal immune pathology in mice [96]. Furthermore, the HOIP-RBR region regulates T-cell and B-cell differentiation.…”
Section: Linear Ubiquitin Chains In the Regulation Of Immune And Cellmentioning
confidence: 99%